Minimal Nasolabial Incision Technique for Nasolabial Fold Modification in Patients With Facial Paralysis - Faris, Callum (JAMA Facial Plast Surg, 2017)
IMPORTANCE: Creation of symmetrical nasolabial folds (NLFs) is important in the management of the paralyzed face. Established techniques use a linear incision in the NLF, and technical refinements now allow the linear incision to be omitted. DESIGN, SETTING, AND PARTICIPANTS: This retrospective case series was conducted in a tertiary care setting from February 2, 2017, to June 7, 2017. Participants were all patients (N = 21) with peripheral facial paralysis who underwent NLF modification that used the minimal nasolabial incision technique at the Massachusetts Eye and Ear Infirmary Facial Nerve Center from February 1, 2015, through August 31, 2016. MAIN OUTCOMES AND MEASURES: Patient-reported outcome measures using the validated, quality-of-life Facial Clinimetric Evaluation (FaCE) Scale; clinician-reported facial function outcomes using a validated electronic clinician-graded facial paralysis assessment (eFACE); layperson assessment of the overall aesthetic outcome of the NLF; and expert-clinician scar assessment of the NLF. RESULTS: Of the 21 patients who underwent NLF modification that used the minimal nasolabial incision technique, 9 patients (43%) were female and 12 (57%) were male. The mean age was 41 (range, 9-90) years; 17 patients (81%) were adults (≥18 years) and 4 (19%) were children (<18 years). Overall, significant improvements were observed after NLF modification in all outcome measures as graded by both clinicians and patients. The mean (SD) scores for total eFACE were 60.7 (14.9) before the operation and 77.2 (8.9) after the operation (mean difference, 16.5 [95% CI, 8.5-24.2]; P < .001). The mean (SD) static eFACE scores were 61.4 (20.6) before the operation and 82.7 (12.4) after the operation (mean difference, 21.3 [95% CI, 10.7-31.9]; P < .001). The mean (SD) FaCE quality-of-life scores were 51.3 (20.1) before the operation and 70.3 (12.6) after the operation (mean difference, 19.0 [95% CI, 6.5-31.6]; P  =  .001). The layperson self-assessment of the overall aesthetic outcome of the NLF modification was higher among the group who had the minimal nasolabial incision than it was for the group who had a historical nasolabial incision (mean [SD], 68.17 [13.59] vs 56.28 [13.60]; mean difference, 11.89 [95% CI, 3.81-19.97]; P < .001). Similarly, the expert-clinician scar assessment of the NLF modification was higher for the group who had the minimal nasolabial incision than it was for the group who had a historical nasolabial incision (3.78 [0.91] vs 2.98 [0.81]; mean difference, 0.80 [95% CI, 0.29-1.32]; P  =  .007). CONCLUSIONS AND RELEVANCE: The minimal nasolabial incision technique for NLF modification is effective in rehabilitating the NLF in facial paralysis without adding a long linear scar to the central midface. LEVEL OF EVIDENCE: 4.